Subject Scheduling Application Using Genetic Algorithm - Wijaya, Benny; Irawadi, Syafrul; Sari, Lili Indah; Probonegoro, Wishnu Aribowo (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
Scheduling is a very important issue in an educational institution. The many obstacles sometimes make scheduling difficult to create. One method for solving such problems is to use genetic algorithms. Based on this background, the formulation of the problem of this study is